HUBUNGAN KEPEMIMPINAN CAMAT DENGAN EFEKTIVITAS KERJA PEGAWAI ( STUDI DI KECAMATAN TOBELO, KABUPATEN HALMAHERA UTARA) - Peleger, Reti; MANDEY, JANTJE; POMBENGI, JERICHO (Sam Ratulangi University, 2014)
This research was conducted with the starting point at the underlying problem,namely whether there is a relationship between leadership effectiveness with the performance ofemployees in district Office Tobelo North Halmahera, with the primary objective to determine therelationship between leadership effectiveness and the performance of employees in district OfficeTobelo North Halmahera.This type of research is survey research, using quantitative and descriptive approach study. Researchvariable is leadership at district and sub-district Employee Performance Tobelo North Halmahera.were collected techniques and informant questionnaires distributed to 20 respondents and analyzedusing simple linear regression analysis techniques.Based on the analysis, it is known that the distribution of respondents on the variable districtemployee performance and leadership in the category of agree and strongly agree. Thus it can beconcluded that the relationship between leadership effectiveness performance of employees in districtOffice Tobelo North Halmahera. Her relationship is so strong that if leader well, then the employee'sperformance will also be good; otherwise if the leader less effective in leading it will affect theperformance of sub-district office employees.Keywords: Head Leadership, Employee Performance